EVENT MARKETING SEBAGAI STRATEGI MENINGKATKAN BRAND AWARENESS KABUPATEN JEMBER - Wulandari, Deasy; Suroso, Imam; Asbullah, Alvan Sidiq (BISMA: Jurnal Bisnis dan Manajemen, 2015)
Abstract: This study aimed to test the effect of event marketing, Visit Jember Month 2012 (Bulan Berkunjung ke Jember 2012 or BBJ 2012),on brand awareness of Jember Regency. The population in this study was the society who saw the BBJ 2012. Snowball sampling was used which resulted in a total of 70 respondents. Multiple linear regressionwas used to test the hypothesis. Results showed that sport and exhibition event marketing did not have a significant effect on the brand awareness of Jember Regency, while art and culture even marketing had a positive and significant effect on the brand awareness of Jember Regency. Keywords: Event Marketing, Brand Awareness, Strategy